Continuous vs. Discontinuous (Teleport) Locomotion in VR: How Implications can Provide both Benefits and Disadvantages - Riecke, Bernhard E; Zielasko, Daniel (IEEE VR Workshop on Finding a way forward in VR locomotion, 2021)
In this short paper we provide a comparative overview of the implications of using continuous vs. discontinuous (teleport) locomotion methods in VR, and argue how many of these implications can provide both benefits and disadvantages depending on the overall goal, desired user experiences, application scenario/context, as well as individual preferences and one’s propensity or cybersickness. We provide a tabular comparison of continuous vs. discontinuous locomotion by comparing and contrasting diverse aspects including accuracy, self-motion cues and sensations, path integration, sensory conflicts, locomotion control, effort, and presence/immersion, and discuss diverse potential benefits and disadvantages of these implications.
Keywords: 2-page conference paper; NSERC DG 2026; Riecke; Riecke_2021; bernhard-riecke; conferencePapers; daniel-zielasko; proj--teleport-vs-continuous; short conference paper